Media Words Card to Improve Reading Skills at the beginning of the First Grade Students in Primary School - Agusalim Agusalim; Suryanti Suryanti; Irwan Irwan (Jurnal Basicedu, 2021)
This study aims to find the use of word cards to improve reading skills at the beginning by using the action class room method. Based on the results of research conducted in 2 cycles. In cycle I showed that through the Use of Word Card Media in Beginning Reading the average value of student learning outcomes obtained was 68.84 and mastery learning reached 53.85% or there were 14 students out of 27 students who had finished learning. These results indicate that in the first cycle the criteria for student learning are not yet completed, because students who score> 65 are only 68.84% smaller than the desired completeness percentage of 85%, and (2) Furthermore, the results of the study cycle II shows through the Use of Word Card Media in Reading the Beginning obtained the average value of student learning outcomes is 76.92 and mastery learning reaches 88.46% or there are 23 students out of 26 students have finished learning. These results indicate that in the second cycle classically students have finished learning, because students who score> 65 are 92.30% greater than the desired completeness percentage of 85%.